Determinants of Managerial Performance: A Cross-cultural Comparison of the Perceptions of Middle-level Managers in Four Countries - Neelankavil, James P.; Mathur, Anil; Zhang, Yong (Journal of International Business Studies, 2000)
This paper examines differences in what affects managerial performance of middle-level managers in four countries—China (N=204), India (N=184), the Philippines (N=220), and the United States (N=176). Important differences were predicted and found in factors affecting managerial performance as perceived by the respondents. While East-West differences exist, significant differences are noted among the three Asian countries. Specifically, Chinese and American managers represented two extremes in their beliefs about what determines managerial performance of middle-level managers. Both Filipino and Indian managers were found more similar to their U.S. counterparts than their Chinese counterparts. Implications of the findings are discussed.